A study on the accountability of the regional R&D program: the case of APCTP - Jinwon Kang; Seongsik Cho (Journal of Open Innovation: Technology, Market, and Complexity, 2016)
In order to develop Asia-Pacific Center for Theoretical Physics (APCTP), it is necessary to respond various kind of accountabilities around research environment as well as research capacity and international reputation. APCTP, the case of this research, has achieved its goal through proper handling of managerial and institutional problems. Simplifying complicated program structure and enhancing efficiency in the managerial level and the stable position of secretary being able to excise practical authority in the institutional level have been based for the sustainable development. While the lack of legal support limited to enhance international reputation, bottomup building of APCTP and volunteer participations and efforts of researchers made good performance as a research platform considering its budget. The previous and present government's emphases on basic research and regional government's support took positive effects to the development of APCTP as international research institute and will provide real help for international reputation in the near future. This paper investigated difficulties around APCTP and their solutions for the sustainable development in terms of technical, managerial and institutional level regarding the open innovation aspect.
Keywords: 650; Regional R&D program; Accountability; Basic research; APCTP